Advances in Metal Supported Cells in the METSOFC EU Consortium1. Issue 4 (18th July 2013) - McKenna, B. J.; Christiansen, N.; Schauperl, R.; Prenninger, P.; Nielsen, J.; Blennow, P.; Klemensø, T.; Ramousse, S.; Kromp, A.; Weber, A.
Abstract The EU‐sponsored project "METSOFC", completed at the end of 2011, resulted in a number of advancements toward implementing a mechanically robust metal support as the structural element in SOFC. Technical University of Denmark (DTU) Energy Conversion's research into planar metal supported cells (MSCs) has produced an advanced cell design with high performance and mechanical robustness. At low operation temperatures (650 °C), these cells have shown low Area‐specific resistances (ASRs): 0.35 Ω cm2 in cell tests (16 cm2 active area) and under 0.3 Ω cm2 in button cells (0.5 cm2 active area). Further success was attained with even larger cell areas of 12 × 12 cm2 squares, which facilitated integration into small stacks at Topsoe Fuel Cell having powers approaching 1/2 kW. Development of MSC stacks showed that the MSCs could achieve similar or better performance, compared to most standard industrial anode supported ceramic cells. The best stacked MSCs had power densities approaching 275 mW cm–2 (at 680 °C and 0.8 V). Furthermore, extended testing at AVL determined extra stack performance and reliability characteristics, including behavior toward sulfur and simulated diesel reformate, and tolerance to thermal cycles and load cycles. These and other key outcomes of the METSOFC consortium are covered, along with associated work supported by the Danish National Advanced Technology Foundation.